Impact of docusate and fauna‐free on feed intake, ruminal flora and digestive enzyme activities of sheep. Issue 4 (7th May 2020) - Yu, Chucai; Luo, Qiujiang; Chen, Yong; Liu, Shimin; Zang, Changjiang
Abstract: Four Small‐tail Han male hogget sheep, fitted with rumen cannula and fed the same basal diet were used to study the impacts of docusate (DOC) and fauna‐free on the voluntary feed intake (VFI), and ruminal protozoal, bacterial and fungal counts and the digestive enzyme activities. By a 4 × 4 Latin square design, sheep were given no DOC (the control), 2 doses of DOC: 1.2 and 3.0 g/kg diet or oral dose of 6.0 g/d DOC for three days (fauna‐free treatment) in each period of 18 days, the last three days of which were for sampling the rumen fluid. Compared with the control, 1.2 g/kg of DOC supplementation significantly resulted in increases of 18.0% VFI and 44% bacterial count, and no significant change in the fungal number. Supplementing DOC reduced protozoal number in a dose‐dependent manner. The fibre degradation enzyme activity in rumen fluid increased by 17.7% with a concomitant 10% increase in volatile fatty acids (VFA); the protease activity was reduced by 23% with a corresponding reduction in rumen ammonia by 42%. In contrast, supplementing 3.0 g/kg of DOC has adverse effects on those measures compared with 1.2 g/kg of DOC. Defaunation was accompanied with substantial increases in the bacterial and fungal counts, but had no significant influences on VFI and the enzyme activity for starch, protein and pectin digestion, and small changes in fibre digestion enzymes and the total VFA compared with the control. A high correlation ( r 2 = 0.82) was noted between VFI and the total activity of fibre digestion enzymes and VFA. It was proposed that fibre digestion rate in the rumen is a primary factor for determining VFI in sheep, and dietary supplementation of 1.2 g/kg of DOC could partially result in enhanced activity of fibre digestive enzyme in the rumen and increase VFI.